2016
DOI: 10.1136/bmjopen-2015-010712
|View full text |Cite
|
Sign up to set email alerts
|

Development of a brief assessment and algorithm for ascertaining dementia in low-income and middle-income countries: the 10/66 short dementia diagnostic schedule

Abstract: ObjectivesTo develop and evaluate a short version of the 10/66 dementia diagnostic schedule for use in low-income and middle-income countries.DesignSplit-half analysis for algorithm development and testing; cross-evaluation of short-schedule and standard-schedule algorithms in 12 community surveys.Settings(1) The 10/66 pilot sample data set of people aged 60 years and over in 25 international centres each recruiting the following samples: (a) dementia; (b) depression, no dementia; (c) no dementia, high educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…The 10/66 short schedule is identical to the original 10/66 schedule 22 in its inclusion of the Community Screening Instrument for Dementia and CERAD 10-word list recall task, but substitutes the Euro-D depression instrument for the longer Geriatric Mental State (of which the Euro-D is a subcomponent). As recently published 19 , the 10/66 short schedule retains high sensitivity and specificity for dementia ascertainment (on data from 25 international centres) and was comparable to the longer instrument in dementia prevalence estimation across previous 10/66 surveys (on data from 16 536 participants in 12 sites from eight countries). All components of the algorithm and the source instruments have been published in an open access source.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…The 10/66 short schedule is identical to the original 10/66 schedule 22 in its inclusion of the Community Screening Instrument for Dementia and CERAD 10-word list recall task, but substitutes the Euro-D depression instrument for the longer Geriatric Mental State (of which the Euro-D is a subcomponent). As recently published 19 , the 10/66 short schedule retains high sensitivity and specificity for dementia ascertainment (on data from 25 international centres) and was comparable to the longer instrument in dementia prevalence estimation across previous 10/66 surveys (on data from 16 536 participants in 12 sites from eight countries). All components of the algorithm and the source instruments have been published in an open access source.…”
Section: Methodssupporting
confidence: 57%
“…All components of the algorithm and the source instruments have been published in an open access source. 19 …”
Section: Methodsmentioning
confidence: 99%
“…obtained using the original algorithm (Stewart et al, 2016). Given the established validity of this 97 approach, as we would expect, distribution of cognitive test scores between our qualitative sampling 98 frame and study participants without dementia were consistent with differences identified in studies 99 carried out elsewhere in sub-Saharan Africa (Guerchet et al, 2010).…”
supporting
confidence: 68%
“…Participants aged 70+ years were sampled from the Kintampo Health and Demographic Surveillance System's database. The 10/66 short dementia diagnostic schedule (comprising of a household questionnaire, Euro-D, a background sociodemographic and risk factor interview, a cognitive test battery, and an in-Dementia research needs in Ghana: a perspective formant interview) 16 , 17 was administered to participants in their homes. A total of 761 participants agreed to participate and were interviewed for the first part of the aim (quantitative component).…”
Section: Kintampo Dementia Initiativementioning
confidence: 99%